Pengaruh Penggunaan Tanah Laterit dan Kapur Padam Terhadap Kuat Tekan Mortar Geopolymer - Sayful Sayfullah (Jurnal Ilmiah Telsinas, 2022)
In numerous locations of Indonesia, such as Papua, Sulawesi, and Kalimantan, there is an abundance of laterite soils, hence they have significant potential as construction materials. Geopolymer concrete and mortar have the potential to minimize the usage of Portland cement because their mechanical qualities are nearly identical to those of Portland cement-based concrete, which needs a considerable deal of energy to produce. This study examines the employment of fly ash and alkaline activators, specifically NaOH and Na2SiO3, as materials to bind lateritic soil by adding slaked lime in order to make concrete and geopolymer mortar with reduced oven use. The ratios of lateritic soil to quenched lime were 95%:5%,and 90%:10%, respectively. Flow tests conducted on fresh geopolymer mortar revealed that all ingredients were able to bond effectively and that no segregation occurred. The specimens were treated or dried in the laboratory without immersion for 3, 7, and 28 days (Laboratory Air Curing). The compressive strength test was analyzed in order to assess the geopolymer mortar's behavior. The test findings revealed that the compressive strength increased from 3 days to 7 days and 28 days. The test findings indicate that the compressive strength obtained at a ratio of 90% lateritic soil to 10% slaked lime is greater than the compressive strength obtained at a ratio of 95% lateritic soil to 5% slaked lime.